A Capability Model for Digital Preservation. Analyzing Concerns, Drivers, Constraints, Capabilities and Maturities - Becker, C. (2011)
The last decade has seen a number of reference models and compliance criteria for Digital Preservation (DP) emerging. However, there is a lack of coherence and integration with standards and frameworks in related fields such as Information Systems; Governance, Risk and Compliance (GRC); and Organizational Engineering. DP needs to take a holistic viewpoint to accommodate the concerns of information longevity in the increasingly diverse scenarios in which DP needs to be addressed. In addition to compliance criteria, maturity models are needed to support focused assessment and targeted process improvement efforts in organizations. To enable this holistic perspective, this article discusses the question of capability maturity and presents a capability model for DP.We further demonstrate how such an architectural approach can be used as a basis to analyze the impact of criteria and metrics from the ISO Repository Audit and Certification standard on stakeholders, concerns, drivers, goals, and capabilities. The analysis presented here shall contribute to advance the understanding of cross-cutting concerns and the discussion on maturity models in DP.